Arctic art and material culture:Northern knowledge and cultural resilience in the northernmost Europe - Huhmarniemi, Maria; Jokela, Timo (2020)
‘Handmade’, place-making, revitalisation and regional development are topical themes in the research of art and culture in the Arctic. The revitalisation of traditions through contemporary crafting has become a featuring approach in the Arctic, corresponding to global interest in materiality. The concept of Arctic art is used in this article to describe art, crafts, design and cultural productions that transmit the material and cultural heritage of Arctic nature and the northern knowledge system related to tactile situated knowing in northernmost Europe. Long-term art-based action research has been carried out in collaboration with the Arctic Sustainable Art and Design (ASAD) network of the University of the Arctic to promote art, culture and education for Arctic sustainability. A few case studies presented in this article were art exhibitions, and the art productions that were shown in the 2019 Arctic Arts Summit (AAS) in Rovaniemi, Finland. In the present work, we discuss the knowledge studied, illustrated and debated in contemporary art productions in the AAS 2019. We conclude that the northern knowledge system is formed in situated learning in relation to local ecocultures, traditions and diverse Indigenous and non-Indigenous cultures. Northern knowledge can be adopted by newcomers and even guests when participating in ecocultures. Artists inform, educate and transform their global audiences by sharing and presenting northern knowledge and different ways of knowing. Research on the ‘handmade’, place-making, revitalisation and knowledge themes has relevance for policy making, contemporary art, arts research and art education on many levels. ‘Handmade’, place-making, revitalisation and regional development are topical themes in the research of art and culture in the Arctic. The revitalisation of traditions through contemporary crafting has become a featuring approach in the Arctic, corresponding to global interest in materiality. The concept of Arctic art is used in this article to describe art, crafts, ...